Development of artistic expression in deaf and hard of hearing preschool children (Heritage, 2023)
This paper discusses the development and specifics of artistic expression in deaf and hard-of-hearing preschool children. We analyzed the significance of the stages of artistic development and the therapeutic effect of artistic expression. A drawing made by a deaf or hard-of-hearing child provides the opportunity to assess their cognitive, social, emotional, and physical development, the development of perception, a sense of beauty, and creativity. Through expressive and aesthetic development, children expand their knowledge and skills in nonverbal, visual, auditory, sensory, and verbal experiences. The artistic expression of deaf and hard-of-hearing children does not lag behind that of a hearing child. Visual representations of children with hearing impairment are much more realistic than those of hearing children. Visual perception of deaf and hard-of-hearing children contains many details related to physiognomy, movement, facial expression, body posture, and color. Children use art to communicate with themselves and the environment. In deaf and hard-of-hearing preschool children, it is necessary to develop all functions of nonverbal and verbal communication through artistic expression.
Keywords: artistic expression, development, deaf and hard of hearing children, preschool age